2022
DOI: 10.1007/s10072-021-05807-w
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital and out-of-hospital stroke in patients with COVID-19: two different diseases?

Abstract: Background Ischemic stroke is a known complication of COVID-19. It may have a different pathogenesis and worse outcome compared to stroke in patients without COVID-19. Furthermore, patients with COVID-19 and out-of-hospital stroke onset might have different characteristics compared to patients with COVID-19 and in-hospital stroke onset. The aim of our study was to analyze the characteristics of patients with stroke with and without COVID-19 and of patients with COVID-19 with in-hospital and out-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Most pediatric studies investigating COVID-19-related AIS have focused on the acute infectious phase, 23 25 with delayed AIS during the postinfectious phase being less commonly described. 10 11 Our study showed that AIS is associated with prior SARS-CoV-2 infection, which adds to the growing evidence of delayed post-COVID AIS. Similarly, several reports described children developing AIS 3 to 8 weeks after resolution of SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…Most pediatric studies investigating COVID-19-related AIS have focused on the acute infectious phase, 23 25 with delayed AIS during the postinfectious phase being less commonly described. 10 11 Our study showed that AIS is associated with prior SARS-CoV-2 infection, which adds to the growing evidence of delayed post-COVID AIS. Similarly, several reports described children developing AIS 3 to 8 weeks after resolution of SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 60%
“…Indeed, several studies showed an increased risk of AIS in patients with higher COVID-19 severity. 26 In the same vein, Ciolli et al 10 and Katz et al 11 reported that patients with in-hospital AIS related to severe COVID-19 had worse clinical outcomes and higher levels of inflammatory and procoagulant markers than patients with out-of-hospital AIS and asymptomatic or mild COVID-19. However, several studies have shown that AIS may occur even in patients with no or minimal symptoms of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations